Behavior of Jatropha curcas L. seeds under osmotic stress: germination and cell cycle activity - Cristiane Dantas de Brito; Marta Bruno Loureiro; Clarissa Abreu Santosw Teles; Mariane Ruzza Schuck; Luzimar Gonzaga Fernandez; Renato Delmondez de Castro (Acta Scientiarum. Agronomy, 2015)
Jatropha curcas is an oil-rich Euphorbiaceae seed species renowned for its apparent tolerance to environmental stresses. It is considered a promising source of renewable feedstock for biodiesel production in the Brazilian semiarid region where crop establishment requires a better understanding of the mechanisms leading to proper seed and plant behavior under water restrictive conditions. This study describes physiological and cytological profiles of J. curcas seeds imbibed in water restriction conditions by means of osmotic stress or osmoconditioning. Seeds were characterized by size, weight, moisture content and dry mass, germinability, and cell cycle activation by means of tubulin and microtubule cytoskeleton accumulation. Osmoconditioning at -0.8 MPa did not induce priming effects as it did not improve the physiological quality of the seed lots. Western blotting and immunocytochemical analysis revealed an increasing accumulation of tubulin and microtubule cytoskeleton in seeds imbibed in water for 48h onwards, culminating in the onset of mitotic configurations after germination. Only cortical microtubules were observed during seed osmoconditioning, whereas mitotic microtubules only occurred after re-imbibition of osmoconditioned seeds in water and subsequent germination.